Penerapan Model Pembelajaran TGT (Teams Games Tournament) dan TGfU (Teaching Games for Understanding) terhadap Motivasi Belajar pada Materi Keterampilan Kebugaran Jasmani - Alifia, Esty; Muhammad, Heryanto Nur; Hidayat, Taufiq (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
Physical Education, Sports and Health (PJOK) is an integral part of the education system that provides knowledge and skills in the field of physical activity and sports. TGT is a cooperative learning model about democratic values ​​by implementing a learning model based on the agreement of members of the group. The TGfU learning model or Teaching Games for Understanding is a game-based learning model. This learning model is dynamic so that in its application, participants will gain several masteries at once, namely mastery of knowledge, skills, strategies and tactics, game rules, and mastery of the game context. The aim of this research is to analyze the TGT and TGfu learning models on the level of student motivation in physical fitness skills material, for grade 4 students at SDN Suko 2 Sidoarjo. It is hoped that the results of this research can be used by practitioners as evaluation material for science in the field of science that has been implemented with the benefits of TGT and TGfu learning models. This research uses quantitative research with a quasi-experimental method (Quasi experiment) with the design of this research using Randomized Control group pretest-posttest Design. The analysis used is average (mean), standard deviation, normality test and T test. The results of this research after being tested with Paired Samples Statistics and the T Test are that there is a significant influence on learning the TGT and TGFu models with a mean TGT of 58.57 at the pre-test and 73.47 at the post-test and a mean TGFu of 59.67 at the during the pre test and 73.23 during the post test.